Pyoderma Gangrenosum, A Rare Chronic Painful Ulcer (Revista de Medicina Clinica, 2024)
Pyoderma Gangrenosum (PG) is a non-infectious, ulcerative inflammatory dermatosis characterized by progressive lesions associated with autoimmune and autoinflammatory phenomena, making its diagnosis a challenge. Pathophysiologically, there are various theories involving genetic predisposition, neutrophil dysfunction, inflammatory mediators and T-cell mediation with complement activation. Since there are no specific biomarkers or characteristic histopathological findings for its diagnosis, the PARACELSUS diagnostic criteria were applied as they have proven to be highly useful in clinical practice. This paper outlines the case of a 62-year-old female patient who presented with gastrointestinal bleeding secondary to chronic NSAID use, due to a chronic ulcer on the posteromedial aspect of the distal third of the right lower limb, with undefined borders and hyperalgesia to touch; the ulcer showed no response to daily wound care, with progression in both depth and diameter. Additional findings included a decrease in the levels of hemoglobin with impaired renal function suggestive of prerenal compromise and a biopsy of the ulcer showing suppurative inflammation. Based on the described findings, the diagnostic criteria were met, linking the dermatological condition to PG. Therefore, immunosuppressive management was initiated with systemic corticosteroid therapy, a calcineurin inhibitor, and local wound care following the TIME principles (Tissue, Infection, Moisture, Edges), with an adequate short and long-term response. As we can see, the management is complex since its diagnosis involves an interrelation of clinical and histopathological characteristics, and its treatment is equally challenging, with a 70% relapse rate despite adequate systemic immunosuppressive therapy. Hence, early clinical suspicion and multidisciplinary management are key to reducing morbidity and mortality.
Keywords: Painful ulcer; Neutrophilic dermatosis; Pathergia; Autoimmune